2010
DOI: 10.1056/nejmoa1009744
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Anacetrapib in Patients with or at High Risk for Coronary Heart Disease

Abstract: Treatment with anacetrapib had robust effects on LDL and HDL cholesterol, had an acceptable side-effect profile, and, within the limits of the power of this study, did not result in the adverse cardiovascular effects observed with torcetrapib. (Funded by Merck Research Laboratories; ClinicalTrials.gov number, NCT00685776.).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
438
3
12

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 694 publications
(461 citation statements)
references
References 19 publications
8
438
3
12
Order By: Relevance
“…It is noteworthy that PCSK9 inhibitors have shown promising results with respect to significantly lowering both Lp(a) and LDL‐C and may serve as the future preferred treatment strategy for patients with familial hypercholesterolemia with combined elevations of Lp(a) and LDL‐C 34, 35, 37. Anacetrapib, the only cholesteryl ester transfer protein inhibitor currently under investigation, has also been suggested to effectively reduce both LDL‐C and Lp(a) levels 38. In contrast, Lp(a)‐lowering agents such as tibolone,39 as well as recent antisense therapies could potentially be used as the primary approach to treat individuals with isolated high Lp(a) levels 36.…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that PCSK9 inhibitors have shown promising results with respect to significantly lowering both Lp(a) and LDL‐C and may serve as the future preferred treatment strategy for patients with familial hypercholesterolemia with combined elevations of Lp(a) and LDL‐C 34, 35, 37. Anacetrapib, the only cholesteryl ester transfer protein inhibitor currently under investigation, has also been suggested to effectively reduce both LDL‐C and Lp(a) levels 38. In contrast, Lp(a)‐lowering agents such as tibolone,39 as well as recent antisense therapies could potentially be used as the primary approach to treat individuals with isolated high Lp(a) levels 36.…”
Section: Discussionmentioning
confidence: 99%
“…188,189,190 Anacetrapib is the only CETP inhibitor, which is under ongoing phase 3 trial investigation for efficacy in preventing clinical endpoints. In the DEFINE (Determining the Efficacy and Tolerability of CETP Inhibition with AnacEtrapib) trial including 1623 patients with known cardiovascular heart disease or at high risk of CHD, co-administration of anacetrapib 100 mg once daily with a statin for 24 weeks provided an additional 40% reduction in LDL-cholesterol and 138% increase in HDL-cholesterol compared with the statin plus placebo group, 191 irrespective of the patient subgroup. 192 A post hoc analysis found that 2.0% of anacetrapib-and 2.6% of placebo-treated subjects experienced a primary end-point at 76…”
Section: Fibratesmentioning
confidence: 99%
“…191 The ongoing Randomized Evaluation of the Effects of Anacetrapib Through Lipidmodification (REVEAL) trial that aims to assess whether anacetrapib (100 mg/day) reduces cardiovascular events among statin-treated patients with a history of cardiovascular disease is ongoing. The results of this study will have to awaited before one can conclude whether CETP inhibition in general is the wrong strategy or whether the specific compound or patient groups determines clinical utility of CETP inhibition.…”
Section: Fibratesmentioning
confidence: 99%
“…These compounds do not affect aldosterone secretion. In the Determining the Efficacy and Tolerability of CETP Inhibition with Anacetrapib (DEFINE) trial, anacetrapib was not found to raise blood pressure, 100 whereas in the dal-OUTCOMES trial, dalcetrapib was found to do so in a minor but statistically significant manner. 10 Furthermore, in the dal-VESSEL trial, dalcetrapib did not impair flow-mediated vasodilation, an index of endothelial function in humans in vivo.…”
Section: Novel Cetp Inhibitorsmentioning
confidence: 99%
“…10 By contrast, CRP was unaffected by anacetrapib in DEFINE trial; in fact, it tended to be slightly higher in the treatment than in the placebo group. 100 As such, it is not surprising that the dal-HEART program was stopped by Roche on May 14, 2012, after an interim analysis Figure 6. Schematic representation of high-density lipoprotein (HDL) metabolism.…”
Section: Novel Cetp Inhibitorsmentioning
confidence: 99%